Phacoemulsification in High Myopia with Silicon Filled Eye - Bondan Harmani; Andi Arus Victor (Majalah Oftalmologi Indonesia, 2015)
High myopia is a pathologic condition which has different anatomy from emmetropic eyes. The elongated vitreous chamber were increasing the shear stress of vitreous and retina, giving risk to several vitreoretinal disorders especially retinal detachment (RD). The extensive and complicated RD that happened in high myopic eyes make pars plana vitrectomy with silicon oil (SO) tamponade more preferable. Unfortunately, treatment of RD in high myopic eyes, especially with SO increase the incidence of cataract. The incidence of cataract in SO filled eyes is nearly 100% if the SO remains for several times. This paper reviews these issue, presenting the way to treat cataract in high myopic SO filled eye effectively with combination of phacoemulsification and SO removal with IOL implantation, helped with the usage of IOL Master. Â Keywords: phacoemulsification, high myopia, silicon filled eye